Kekerasan terhadap Perempuan dan Anak di Pademangan Barat: Kritik atas Kebisuan Hukum dan Peluang Pembebasan - Sari, Rosalina Indah; Gefaro, Al Gidzar; Fung, Piong Khoy; Harvelian, Agnes (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
This community service activity aims to respond to the legal silence that still surrounds vulnerable groups in Pademangan Barat Village, North Jakarta, particularly women and children who are often victims of domestic violence. In a social context marked by patriarchal structures and low legal literacy, violence is often considered part of household dynamics rather than a violation of the law. The one-day legal education session held at the Integrated Child-Friendly Public Space (RPTRA) was an initial intervention designed in a participatory and community-based manner. The activity not only conveyed legal material in a normative manner but also encouraged residents to reflect on their social experiences in open discussions with community leaders and local officials. The most notable outcome of this activity is the increased legal awareness among local residents. Additionally, there has been a change in attitude identified verbally through participants' courage to ask critical questions, share personal experiences, and challenge social norms that have long silenced victims. This phenomenon underscores that legal education, when conducted through a dialogic approach as suggested by Freire (2005), can serve as an initial instrument for social transformation, even within limited spatial and temporal constraints. This activity demonstrates that law does not necessarily begin in the courtroom but can emerge from honest, simple conversations within the community.